Equality of Dedekind sums modulo 72Z - Salman, Shatha A.; Hadeed, Iman S. (Iraqi Journal of Science, 2021)
According to the wide appearance of Dedekind sums in different applications on different subjects, a new approach for the equivalence of the essential and sufficient condition for ( ) ( ) in and ( ) ( ) in where ( ) Σ(( ))(( )) and the equality of .two .Dedekind sums with their connections is given. The conditions for ( ) ( ) in which is equivalent to ( )– ( ) in were demonstrated with condition that of does not divide . Some applications for the important of Dedekind sums were given.